Pengaruh Kedisiplinan Dan Budaya Organisasi Terhadap Kinerja Pegawai Dinas Koperasi Dan Usaha Kecil Menengah Kabupaten Kolaka - Gaprilla Gaprilla; Fitri Kumalasari; Suwarto Suwarto (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
This study aims to determine: (1) The Effect of Discipline on Employee Performance of the Kolaka Regency Cooperative and Small and Medium Enterprises Office, (2) The Effect of Organizational Culture on Employee Performance of the Kolaka Regency Cooperative and Small and Medium Enterprises Office. The sample in this study amounted to 39 respondents using the sampling technique, namely the census. Research instrument testing using validity test and reliability test with SPSS 22.0. The research data analysis technique uses the Structural Equation Modeling (SEM-PLS) method with SmartPLS 4.0. Based on the results of this study, it can be seen that the Discipline variable has a positive and significant effect on Employee Performance as shown by the T-Statistic value of 2.810 and P-Values of 0.002, variables and organizational culture variables have a positive and significant effect on Employee Performance as shown by the T-Statictic value of 1.828 and P-Values of 0.034.